Advances in the Study of Greek: new insights for reading the New Testament - Campbell, Constantine R. (Zondervan, 2015)
This books examines issues of interest in the current world of Greek scholarship and provides an accessible introduction for students, pastors, professors, and commentators to understand these issues in this period of paradigm shift